The association between ambient air pollution control and stroke mortality during the 2010 Asian Games in Guangzhou, China. (15th November 2019) - Zhang, Shiyu; Lv, Jiayun; Meng, Ruilin; Yang, Yin; Acharya, Bipin Kumar; Sun, Xiangyan; Lin, Hualiang; Hu, Qiansheng; Ruan, Zengliang
Abstract: Although ambient air pollution has been consistently associated with morbidity and mortality of stroke, there is limited evidence on whether the control of air pollution would associate with a reduced risk of stroke. The citywide air pollution controlling measures during the 2010 Asian Games in Guangzhou provided such an opportunity to answer this question. We collected daily data on the concentrations of air pollutants and mortality from ischemic and hemorrhagic stroke, and compared them for 51 intervention days in 2010 with the corresponding days in 2006–2009 and 2011 (reference period). Poisson-based interrupted time series analysis was employed to estimate the relative risk (RR) and 95% confidence interval (CI). The daily mean concentrations of PM10 (particles with an aerodynamic diameter smaller than 10 μm) was 88.64 μg/m 3 during the reference period, and 80.47 μg/m 3 during the intervention period. Daily mortality number of total stroke, ischemic and hemorrhagic stroke decreased from 3.67, 2.00 and 1.67 during the reference period, to 3.00, 1.76 and 1.24 during the intervention period; the corresponding RR was 0.79 (95% CI: 0.66–0.94), 0.87 (95% CI: 0.69–1.11) and 0.69 (95% CI: 0.52–0.91), respectively. Our findings show that ambient air pollution controlling measures during the 2010 Asian Games in Guangzhou were associated with a decreased risk of stroke mortality, which suggests a need to reduce air pollution to improve public health. Highlights: We examined the association between air pollution control and stroke mortality. Air pollution and stroke mortality decreased after the control program. Air pollution control was associated with a decreased risk of stroke mortality. This association was more pronounced for hemorrhagic stroke mortality.